The self-assessment of lifestyle and prevention of breast cancer on the example of female students from selected high schools in Tricity - Książek, Janina; Habel, Agnieszka; Cieszyńska, Marta; Kruk, Agnieszka (Polish Journal of Public Health, 2013)
Introduction. Breast cancer is one of the most frequently diagnosed female malignancies in Poland and worldwide. Detection of the disease at its early stages increases the probability of recovery. Obeying the rules of healthy lifestyle, participation in mammographic screening, and self-examination of breasts play vital role in breast cancer prevention.Aim. To analyze the health-related behaviors regarding breast cancer prevention among the female students of higher education institutions from Tricity.Material and methods. The study included 168 female students of the Medical University of Gdansk, University of Gdansk, Gdansk University of Technology, and Gdansk Higher School of Humanities, and was conducted between March and June 2010. We used the method of diagnostic survey, and relationships between studied variables were determined on the basis of Pearson’s coefficient of linear correlation.Results. Our study revealed that the group of students from selected Gdansk higher education institutions present satisfactory level of knowledge with regards to health-related behaviors, self-examination of breast, and mammographic screening. Despite possessed knowledge, our students do not self-examine their breasts, and their diet is not sufficiently balanced. Moreover, our findings suggest that the issue of drinking alcohol by women cannot be ignored.Conclusions. The lack of breast self-examination habit among the students of Gdansk higher education institutions points to the inefficiency of existing education programs. This fact should be acknowledged by healthcare professionals, including nurses and midwives